Permanent Genetic Resources added to Molecular Ecology Resources Database 1 December 2012–31 January 2013. (25th March 2013) - ,; Arranz, Silvia E.; Avarre, Jean‐Christophe; Balasundaram, Chellam; Bouza, Carmen; Calcaterra, Nora B.; Cezilly, Frank; Chen, Shi‐long; Cipriani, Guido; Cruz, V. P.; D'Esposito, D.; Daniel, Carla; et al.
Abstract This article documents the addition of 268 microsatellite marker loci to the Molecular Ecology Resources Database. Loci were developed for the following species: Alburnoides bipunctatus, Chamaerops humilis, Chlidonias hybrida, Cyperus papyrus, Fusarium graminearum, Loxigilla barbadensis, Macrobrachium rosenbergii, Odontesthes bonariensis, Pelteobagrus vachelli, Posidonia oceanica, Potamotrygon motoro, Rhamdia quelen, Sarotherodon melanotheron heudelotii, Sibiraea angustata, Takifugu rubripes, Tarentola mauritanica, Trimmatostroma sp. and Wallago attu. These loci were cross‐tested on the following species: Alburnoides fasciatus, Alburnoides kubanicus, Alburnoides maculatus, Alburnoides ohridanus, Alburnoides prespensis, Alburnoides rossicus, Alburnoides strymonicus, Alburnoides thessalicus, Alburnoides tzanevi, Carassius carassius, Fusarium asiaticum, Leucaspius delineatus, Loxigilla noctis dominica, Pelecus cultratus, Phoenix canariensis, Potamotrygon falkneri, Trachycarpus fortune and Vimba vimba.